1994
DOI: 10.1146/annurev.mi.48.100194.002235
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomaviruses

Abstract: During the past 17 years 73 genotypes of human pathogenic papillomaviruses (HPV) have been identified. Most of them are found in benign proliferations; however, several have been discovered in malignant tumors. Specifically, cancer of the cervix, other anogenital cancers, but also some cancers of the skin, the oral and nasal cavity, and the rare periungual carcinomas have been linked to specific HPV infections. The pathogenesis of cancer of the cervix has been particularly well studied. Specific viral genes (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
254
0
9

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(270 citation statements)
references
References 0 publications
3
254
0
9
Order By: Relevance
“…37 Historically, evidence of the carcinogenic role of HR HPVs is based on 2 oncoproteins: HPV-E6, which promotes degradation of the p53 tumor-suppressor gene product, 38 and HPV-E7, which modifies pRb tumor-suppressor gene product function, leading to increased cell proliferation and contributing to carcinogenesis. 39,40 In a review on epidemiologic and molecular bases, Ha and Califano 41 attrib- uted to HR HPV a role in oral carcinogenesis but only in a small subset of cases, with differences reported in clinical outcome, response to radiotherapy and prognosis. 21,22,33,[42][43][44][45] In this context, it becomes important to identify this cluster principally on the basis of key immunohistochemical cell cycle markers that are inexpensive and reliable, such as PCNA, MIB-1 and survivin.…”
Section: Discussionmentioning
confidence: 99%
“…37 Historically, evidence of the carcinogenic role of HR HPVs is based on 2 oncoproteins: HPV-E6, which promotes degradation of the p53 tumor-suppressor gene product, 38 and HPV-E7, which modifies pRb tumor-suppressor gene product function, leading to increased cell proliferation and contributing to carcinogenesis. 39,40 In a review on epidemiologic and molecular bases, Ha and Califano 41 attrib- uted to HR HPV a role in oral carcinogenesis but only in a small subset of cases, with differences reported in clinical outcome, response to radiotherapy and prognosis. 21,22,33,[42][43][44][45] In this context, it becomes important to identify this cluster principally on the basis of key immunohistochemical cell cycle markers that are inexpensive and reliable, such as PCNA, MIB-1 and survivin.…”
Section: Discussionmentioning
confidence: 99%
“…One study identified a correlation between replication-dependent histone mRNA polyadenylation and p53 status in head and neck squamous cell carcinomas (Yan et al, 2007), while another study identified a downregulation in the expression of polyadenylated replication-dependent histone mRNAs in human papilloma virus-positive (HPV þ ) squamous cell carcinoma of the head and neck (Martinez et al, 2007). As p53 is a primary target of the HPV E6 oncoprotein (zur Hausen and de Villiers, 1994), it is possible that the changes observed in the second study were also due to regulation of p53 function. Therefore, we tested whether the accumulation of p53 affects replication-dependent histone pre-mRNA 3 0 end processing by treating wild-type (p53 þ / þ ), p53 null (p53À/À) or p21 null (p21À/À) HCT116 cells with Nutlin-3a, which increases endogenous p53 protein levels by blocking the interaction with its negative regulator murine double minute-2 (MDM2).…”
Section: P53mentioning
confidence: 99%
“…The human papilloma viruses (HPV) are a group of epitheliotropic small DNA viruses that have been strongly linked to the etiology of human anogenital cancer, particularly cervical cancer (Mansur and Androphy, 1993;Zur-Hausen and de Villiers, 1994;Stoler, 2000). Indeed, 99.7% of invasive cervical carcinomas worldwide contain and express DNA from HPV (Walboomers et al, 1999;Herrington, 1999), with HPV-16 and 18 being the types most frequently found in these tumors.…”
Section: Introductionmentioning
confidence: 99%